From Soft Power to Sports Economy: The Global Significance of Zheng Qinwen’s Olympic Victory in Chinese Tennis - Wang, Xinrui (Journal of World Economy, 2025)
The rise of China as a powerhouse in the international sports arena has dramatically changed its image and cultural influence abroad. Traditionally known for its economic might and political moves, China has used sports as a strategic tool to project its cultural narrative and increase its soft power. Tennis, traditionally considered a Western sport, has become a significant factor in China’s sports diplomacy, representing modernization and cultural integration. Its outstanding achievements in tennis, such as those made by Zheng Qinwen, have challenged the Western monopoly on the sport and inspired a new generation of Chinese athletes. The national pride fostered by such achievements has drawn international recognition, making China a formidable competitor in a sport that was once considered a monopoly of Western nations. Additionally, commercialization and international positioning have turned tennis into a synonym for luxury, thus influencing the attitude of people and the level of participation in China. This paper discusses how tennis has been able to shape China’s sports image internationally, starting from its historical roots, moving on to its global positioning, and finally turning it into a symbol of wealth and prestige. It also examines how the success of China in tennis has reoriented its international narrative, increasing its cultural presence and repositioning it within the global pecking order of sport.